The effects of low-load vs. High-load resistance training on muscle fiber hypertrophy: a meta-analysis - Grgic, J. (Journal of Human Kinetics, 2020)
The aim of this meta-analysis was to explore the effects of low-load vs. high-load resistance training on type I and type II muscle fiber hypertrophy. Searches for studies were performed through ten databases. Studies were included if they: (a) compared the effects of low-load vs. high-load resistance training (performed to momentary muscular failure); and, (b) assessed muscle fiber hypertrophy. A random-effects meta-analysis was performed to analyze the data. Ten study groups were included in the analysis. In the meta-analysis for the effects of low-load vs. high-load resistance training on type I muscle fiber hypertrophy, there was no significant difference between the training conditions (standardized mean difference: 0.28; 95% confidence interval: -0.27, 0.82; p = 0.316; I2 = 18%; 95% prediction interval: -0.71, 1.28). In the meta-analysis for the effects of low-load vs. high-load resistance training on type II muscle fiber hypertrophy, there was no significant difference between the training conditions (standardized mean difference: 0.30; 95% confidence interval: -0.05, 0.66; p = 0.089; I2 = 0%; 95% prediction interval: -0.28, 0.88). In this meta-analysis, there were no significant differences between low-load and high-load resistance training on hypertrophy of type I or type II muscle fibers. The 95% confidence and prediction intervals were very wide, suggesting that the true effect in the population and the effect reported in a future study conducted on this topic could be in different directions and anywhere from trivial to very large. Therefore, there is a clear need for future research on this topic.